Susceptibility of various Gladiolus cultivars to fluoride pollution and their suitability for bioindication - Klumpp, Andreas; F. Modesto, Irene; Domingos, Marisa; Klumpp, Gabriele (Pesquisa Agropecuaria Brasileira, 1997)
Ten Brazilian cultivars of Gladiolus, a widely used bioindicator plant of fluoride pollution, were exposed to ambient air at a severely fluoride-polluted site and a reference site near the industrial complex of Cubatão, SP, Brazil, in order to determine their sensitivity and to select cultivars with adequate bioindication characteristics. Assessment of pollution-induced effects included quantitative evaluation of leaf injuries, determination of leaf and flower dry weight as well as analysis of foliar fluoride concentrations. Plants exposed at the polluted site showed necroses at tips and margins of the leaves, typically caused by fluoride on this species. Intensity and distribution of lesions on the blades varied between the cultivars. Fluoride pollution resulted in accumulation of fluoride in leaves. Dry weight of leaves and flowers of plants exposed at the polluted site were significantly reduced when compared with the reference site. Considering sensitivity and evaluability of leaf injuries; the cultivars White Friendship and Eurovision are suggested for use as bioindicators of fluoride pollution in tropical/subtropical as well as in temperate regions.